Dietary charcoal supplementation modulates hematological, biochemical, immunological, antioxidant, and intestinal parameters in ducks (Journal of Advanced Veterinary and Animal Research, 2025)
Objective: This study aimed to investigate the impact of dietary charcoal supplementation on hematological and biochemical indices, immune function, antioxidant status, and intestinal histomorphology in ducks. Materials and Methods: A total of 144 mule ducks, aged 4 weeks, were randomly allocated into 6 experimental groups. Birds were reared under uniform conditions in floor pens and provided with a basal diet (3,000 kcal/kg ME and 20% CP)supplemented with 0.0%, 0.5%, 1.0%, 1.5%, 2.0%, or 2.5% charcoal. Results: Dietary inclusion of charcoal at 1.0%, 1.5%, and 2.0% significantly reduced serum creatinine (p = 0.049) and urea concentrations (p = 0.036), suggesting enhanced renal function. Additionally, ducks receiving 1.5% and 2.0% charcoal exhibited significantly lower plasma corticosterone levels (p = 0.045) and elevated blood glucose concentrations (p = 0.042) compared to the control group. No significant differences (p > 0.05) were observed in other serum biochemical markers (total protein, albumin, globulin, albumin-to-globulin ratio, cholesterol, aspartate aminotransferase, and alanine aminotransferase) or hematological parameters. Antioxidant capacity was significantly enhanced (p ≤ 0.05) in ducks fed 1.5% charcoal, except for malondialdehyde levels, which remained unaffected (p = 0.943). Serum immunoglobulin A concentrations and relative spleen weights were significantly higher in the 1.5% and 2.0% charcoal groups (p = 0.0125 and p = 0.0207, respectively), while IgG and IgM levels did not differ among treatments (p > 0.05). Moreover, charcoal supplementation at 1.5%, 2.0%, and 2.5% positively influenced the villus architecture of both the duodenum and cecum (p < 0.05). Conclusion: Dietary supplementation with up to 1.5% charcoal appears to confer physiological benefits in ducks by supporting renal function, enhancing immune and antioxidant responses, and improving intestinal morphology.J. Adv. Vet. Anim. Res., 12(3): 709–716, September 2025http://doi.org/10.5455/javar.2025.l934